YOZMA TARJIMANING SINTAKTIK-SEMANTIK XUSUSIYATLARI (KONFERENSIYA, 2025)
The article examines the lexical, syntactic, and semantic characteristics ofmedical technology English and explores effective translation strategies for renderingthese structures into Uzbek. Special attention is given to the use of passiveconstructions, nominalization, and complex sentence patterns, which are highlyfrequent in scientific and technical medical texts. Through analytical examplesextracted from professional medical discourse, the study identifies key linguisticchallenges and proposes practical solutions for improving translation accuracy,clarity, and scientific objectivity. The findings contribute to enhancing the quality ofmedical translation and ensuring reliable knowledge transfer in healthcarecommunication